In vitro investigation of the mutagenic potential of Aloe vera extracts. Issue 6 (11th August 2014) - Guo, Xiaoqing; Zhang, Suhui; Dial, Stacey L.; Boudreau, Mary D.; Xia, Qingsu; Fu, Peter P.; Levy, Dan D.; Moore, Martha M.; Mei, Nan
Graphical Abstract: Abstract: A 2-year cancer bioassay in rodents with a preparation of Aloe vera whole leaf extract administered in drinking water showed clear evidence of carcinogenic activity. To provide insight into the identity and mechanisms associated with mutagenic components of the Aloe vera extracts, we used the mouse lymphoma assay to evaluate the mutagenicity of the Aloe vera whole leaf extract (WLE) and Aloe vera decolorized whole leaf extract (WLD). The WLD extract was obtained by subjecting WLE to activated carbon-adsorption. HPLC analysis indicated that the decolorization process removed many components from the WLE extract, including anthraquinones. Both WLE and WLD extracts showed cytotoxic and mutagenic effects in mouse lymphoma cells but in different concentration ranges, and WLD induced about 3-fold higher levels of intracellular reactive oxygen species than WLE. Molecular analysis of mutant colonies from cells treated with WLE and WLD revealed that the primary type of damage from both treatments was largely due to chromosome mutations (deletions and/or mitotic recombination). The fact that the samples were mutagenic at different concentrations suggests that while some mutagenic components of WLE were removed by activated carbon filtration, components with pro-oxidant activity and mutagenic activity remained. The results demonstrate the utility of the mouse lymphoma assay as a tool to characterize the mutagenic activity of fractionated complex botanical mixtures to identify bioactive components.